The Relationship Of Knowledge With Sexual Behavior Pregnant Woman Trimester III In The Work Area Of Puskesmas Basuki Rahmad Bengkulu City: Hubungan Pengetahuan dengan Perilaku Seksual Ibu Hamil Trimester III di Wilayah Kerja Puskesmas Basuki Rahmad Kota Bengkulu - Aprilia Ningsih, Dewi; Sanisahhuri, Sanisahhuri; Mulyani, Dwi (Jurnal Kebidanan Midwiferia, 2020)
Sexual intercourse will be better done in the third trimester because the physical and mental conditions of pregnant women support, of course with the right sexual position. This study aims to study the relationship of knowledge with sexual behavior of pregnant women in third trimester in the working area of ​​Puskesmas Basuki Rahmad Bengkulu City.This study uses a cross sectional design. The population in this study were all pregnant women in the third trimester in the working area of ​​the health center, basuki rahmad, bengkulu city. Sample appearance technique in this study uses purposive sampling. A sample of 35 third trimester pregnant women was obtained. data collection in this study uses a questionnaire.The results were obtained: 15 (42.9%) respondents had good knowledge, 24 (68.6%) respondents had sexual intercourse during the third trimester of pregnancy. There was a significant relationship between the knowledge of third trimester pregnant women with third trimester pregnant women sexual behavior. in the Puskesmas Basuki Rahmad Working Area, the City of Bengkulu with the category of moderate relations. To various parties, especially pregnant women in the third trimester to increase their knowledge about sexual relations during the third trimester of pregnancy and for health workers to improve the information provided to pregnant women both in terms of counseling and at the time of pregnancy examination.